A case study of the sizing and optimisation of an energy pile foundation (Rosborg, Denmark). (March 2020) - Alberdi-Pagola, Maria; Poulsen, Søren Erbs; Jensen, Rasmus Lund; Madsen, Søren
Abstract: This paper applies previously validated multiple pile g-functions, for estimating operational average fluid temperatures in an actual energy pile foundation in Rosborg, Denmark. We find that the multiple pile g-functions yield fluid temperatures similar to what is observed, at minimal computational cost. The temperature model is then utilised in an optimisation algorithm that yields the minimum number of energy piles required by simultaneously maximising the pile spacing and taking into consideration the thermal load of the building. The optimisation shows that the thermal needs of the building can be fully supplied by 148 rearranged energy piles, instead of the current 219. The optimisation tool is also applied to a full-factorial design sweep which shows a large sensitivity of the number of energy piles on the thermal conductivity of the ground.